Paternal Induction of Hybrid Dysgenesis in Drosophila melanogaster Is Weakly Correlated with Both P-Element and hobo Element Dosage. - Srivastav, S.P.; Kelleher, E.S. (G3 : genes - genomes - genetics, 2017)
Transposable elements (TEs) are virtually ubiquitous components of genomes, yet they often impose significant fitness consequences on their hosts. In addition to producing specific deleterious mutations by insertional inactivation, TEs also impose general fitness costs by inducing DNA damage and participating in ectopic recombination. These latter fitness costs are often assumed to be dosage-dependent, with stronger effects occurring in the presence of higher TE copy numbers. We test this assumption in Drosophila melanogaster by considering the relationship between the copy number of two active DNA transposons, P-element and hobo element, and the incidence of hybrid dysgenesis, a sterility syndrome associated with transposon activity in the germline. By harnessing a subset of the Drosophila Genetic Reference Panel (DGRP), a group of fully-sequenced D. melanogaster strains, we describe quantitative and structural variation in P-elements and hobo elements among wild-derived genomes and associate these factors with hybrid dysgenesis. We find that the incidence of hybrid dysgenesis is associated with both P-element and hobo element copy number in a dosage-dependent manner. However, the relationship is weak for both TEs, suggesting that dosage alone explains only a small part of TE-associated fitness costs.